Evaluation of Fecal Calprotectin as a Non-Invasive Marker of Disease Activity in Ulcerative Colitis - Zahoor Ahmed Shah, Syed Osama Talat Jalal Khan, Abdul Sadiq, Shahzad Latif, Syed Ehsanullah, Farah Naz Tahir, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
A cross-sectional analysis assessed the diagnostic accuracy of fecal calprotectin (FC) in 200ulcerative colitis (UC) patients undergoing surveillance colonoscopy. FC levels were comparedwith Mayo endoscopic subscore